Maternal caregiving moderates the impact of antenatal maternal cortisol on infant stress regulation. (16th November 2021) - Nazzari, Sarah; Fearon, Pasco; Rice, Frances; Molteni, Massimo; Frigerio, Alessandra
Abstract : Background: Emerging evidence suggests that antenatal exposure to maternal stress signals affects the development of the infant stress response systems. Animal studies indicate that maternal sensitive caregiving can reverse some of these effects. However, the generalizability of these findings to humans is unknown. This study investigated the role of maternal caregiving in the association between multiple markers of maternal antenatal stress and infant stress regulation. Methods: The sample consisted of 94 mother‐infant ( N  = 47 males, mean postnatal weeks = 12; SD  = 1.84) dyads. Maternal levels of Interleukin‐6, C‐Reactive Protein (CRP), diurnal cortisol and alpha amylase, depressive and anxiety symptoms were assessed in late pregnancy (mean gestational age = 34.76; SD  = 1.12), whereas postnatal symptomatology, caregiving, and infant cortisol response to the inoculation were evaluated at 3 months. Results: Hierarchical linear models (HLMs) showed a significant interaction between maternal antenatal cortisol, caregiving, and time on infant cortisol reactivity, while controlling for gender, maternal age, and postnatal depression. Specifically, higher levels of maternal antenatal cortisol were associated with greater cortisol response only among infants of less emotionally available mothers. All other markers of antenatal stress were not significantly associated with infant cortisol reactivity either independently or in interaction with maternal caregiving. Conclusions: Albeit preliminary, results provide the first evidence in humans that maternal sensitive caregiving may eliminate the association between antenatal maternal cortisol and infant cortisol regulation.